Pelatihan interaktif HACCP pada departemen QC PT.Charoen Pokphand Indonesia Food division Berbek Plant Sidoarjo - Putri, Nur Dyah Bela; Jariyah, Jariyah (TEKMULOGI: Jurnal Pengabdian Masyarakat, 2023)
PT Charoen Pokphand Indonesia Food Division Berbek Plant Sidoarjo is a food company with a strong commitment to the safety and quality of its products. Furthermore, to maintain high HACCP standards, it is necessary to increase the HACCP knowledge and awareness of QC staff personnel. The purpose of this service is to increase HACCP knowledge and awareness through interactive training for QC staff at PT Charoen Pokphand Indonesia Food Division Berbek Plant Sidoarjo. The method of this service is carried out by conducting a pre-test, conducting socialization, interactive training, and evaluation which is carried out by conducting a post-test. The pre-test results obtained an average score of 65.4.  While the post-test results, it is known that 90.9% of participants scored above the KKM with an average score of 91.8. Not only the average score, the score of each participant also increased. However, awareness of the application of HACCP is still considered lacking, based on the low case study average score of 47.8. Training involving a combination of theoretical material and practical training helped QC staff gain a better understanding of the principles and application of HACCP.